-18-1,3у=35,9+3,6у
-1,3у-3,6у=35,9+18
-4,9у=53,9
у=53,9:(-4,9)
у=-11
7×(5+у)-4у=4у-56
35+7у-4у=4у-56
7у-4у-4у=-56-35
-1у=-91
у= 91
Пошаговое объяснение:
1.
-1,3у - 3,6у = 35,9 + 18
-4,9у = 53,9
у = 53,9 : (-4,9)
у = -11
2.
35 + 7у - 4у = 4у - 56
7у - 4у - 4у = -56 - 35
-у = -91
у = 91
-18-1,3у=35,9+3,6у
-1,3у-3,6у=35,9+18
-4,9у=53,9
у=53,9:(-4,9)
у=-11
7×(5+у)-4у=4у-56
35+7у-4у=4у-56
7у-4у-4у=-56-35
-1у=-91
у= 91
Пошаговое объяснение:
1.
-1,3у - 3,6у = 35,9 + 18
-4,9у = 53,9
у = 53,9 : (-4,9)
у = -11
2.
35 + 7у - 4у = 4у - 56
7у - 4у - 4у = -56 - 35
-у = -91
у = 91